Correction: New tetranuclear manganese clusters with [MnII3MnIII] and [MnII2MnIII2] metallic cores exhibiting low and high spin ground state. Issue 12 (9th March 2017) - Sobocińska, M.; Antkowiak, M.; Wojciechowski, M.; Kamieniarz, G.; Utko, J.; Lis, T.
Abstract : Correction for 'New tetranuclear manganese clusters with [Mn II 3 Mn III ] and [Mn II 2 Mn III 2 ] metallic cores exhibiting low and high spin ground state' by M. Sobocińska et al., Dalton Trans., 2016, 45, 7303–7311.